Pembelajaran Geografi dan Motivasi Belajar dapat Meningkatkan Sikap Peduli Pelestarian Lingkungan Hidup pada Peserta Didik - Septiningwati, Emy (SCAD Independent, 2023)
The purpose of this study was to determine and analyze the influence of geography learning and learning motivation, combined, on students’ environmental awareness. This study used a survey method, and primary data were obtained from questionnaires distributed to 12th grade social studies students at SMA Negeri 1 Simpang Empat. The results of this study indicate that geography learning and learning motivation, combined, have a positive and significant effect on environmental awareness. Geography learning aims to foster awareness and a sense of responsibility for environmental quality. Therefore, geography teachers are advised to modify their learning strategies to be more meaningful by providing role models in addressing environmental issues in their surroundings.